Plant domestication and the origins of agriculture in the neolithic Near East - ʻAbo, Shaḥal ca. 20./21. Jh; Gōfer, ʾAvī 1969-; Bar-Gal, Gila Kahila ca. 20./21. Jh (Cambridge University Press, 2022)
The Agricultural Revolution - including the domestication of plants and animals in the Near East - that occurred 10,500 years ago ended millions of years of human existence in small, mobile, egalitarian communities of hunters-gatherers. This Neolithic transformation led to the formation of sedentary communities that produced crops such as wheat, barley, peas, lentils, chickpeas and flax and domesticated range of livestock, including goats, sheep, cattle and pigs. All of these plants and animals still play a major role in the contemporary global economy and nutrition. This agricultural revolution also stimulated the later development of the first urban centres. This volume examines the origins and development of plant domestication in the Ancient Near East, along with various aspects of the new Man-Nature relationship that characterizes food-producing societies. It demonstrates how the rapid, geographically localized, knowledge-based domestication of plants was a human initiative that eventually gave rise to Western civilizations and the modern human condition
Keywords: Ethnobotany / Middle East; Agriculture, Prehistoric / Middle East; Neolithische Revolution; Landwirtschaft; Alter Orient